Longitudinal Study on Social Networks as a Didactic Method - Margarita R. Rodríguez-Gallego; Antonia López-Martínez; María José Navarro-Montaño (Pontificia Universidad Javeriana, 2019)
This article gathers the perceptions of students on social networks, as a didactic method, with the aim of searching and designing didactic strategies to adapt the contents and methodology to the new technological context. The parti-cipants were university students of Early Childhood and Primary Education in 2013-2014 and 2016-2017. A longitudinal study was conducted with a descriptive, non-experimental methodology and the semi-structured questionnaire used was validated through factorial and cluster analyses. The students from both degrees showed a polarization and dispersion of opinions about social networks, which could be related to a more critical attitude toward their advantages and disadvantages.